Decision Support System to Determine The Best Motor Modification Tool In Pringsewu Using Analytical Hierarchy Process - Rinawati Rinawati; Stevanus Prihanuji (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Along with the development of the times, the needs of the community is increasing. Similarly, the need for motor modifications, the development of motor modification products at this time has grown so rapidly and a lot of competition, the number of motor modification products on offer will make the stores confused in terms of the most consumer goods, the process of selecting goods modification motor the most popular consumer is the process of obtaining and using information about the best modified motorcycle goods in the modified motor shop in Pringers. A motor modification shop should make the right decisions regarding the selection of the most preferred consumer modification items, if this is done well and correctly will guarantee the results of the selection of quality and consumer demand. Decision support systems play a role in helping shops to make informed decisions. In this research, there are 5 alternative choice of modified goods which are Power, Sharky, SPD, DBS, and YSS merchandise goods, after normalization process for each criteria, the product of motor modification Power as product has value the biggest end.